MAKNA DAN PRAKTEK TRADISI BERSIH DESA DI JOMBANGAN KEDIRI - Nimatul Inayah; M. Thoriqul Huda; Khamdan Sukron (Universum, 2024)
The Bersih Desa tradition is a tradition or culture that is widely practiced by Javanese people, especially in East Java, Jombangan Village is one of the areas in East Java that carries out the Bersih Desa tradition. Jombangan community is a community that is not too thick with kejawen traditions but they do not forget the traditions that have been passed down from generation to generation by their ancestors. Bersih Desa in Jombangan is a form of community gratitude for what has been given by God Almighty, realizing it is by cleaning the entire village, praying together between community groups by reading tahlilan and also istighosah. In the procession of the village clean tradition, the whole community took part in the activity, so they worked together and worked together to realize the village clean event. This research is descriptive qualitative using field research. Data collection was carried out by conducting observations in the village, interviews and documentation to obtain more concrete information about the problem under study. The results of this research in Jombongan show that the people in this village are very enthusiastic in the Bersih Desa tradition event, apart from being a manifestation of gratitude, another thing that is felt in this tradition is that people can stay in touch with each other between neighbors and village communities.